2005
DOI: 10.1108/09513550510608859
|View full text |Cite
|
Sign up to set email alerts
|

The (un)intended outcome of public sector performance measurement

Abstract: PurposeTo consider the extent to which (a) regimes of performance measurement in the public sector are fit for purpose and (b) the likely outcomes for public services and public sector workers of such performance measurement systems. Design/Methodology/ApproachThe article considers 4 key issues: The context and content of performance measurement in the public sector; the specific examples of healthcare and higher education; the limitations of performance measurement systems; the likely outcomes of performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 30 publications
(29 reference statements)
0
110
0
6
Order By: Relevance
“…They identify a number of studies carried out in the 1970s which suggested that the key motivations for students were based around issues such as "intellectual discovery", a "desire for knowledge" and "enthusiasm" (p.3) and argue that, for a number of reasons, this type of motivation is being eroded and replaced by more instrumental motivations whereby education has become "a means towards some end, rather than being valuable in its own right" (p.3). This is a reasonable reflection of a broad cross section of the literature which examines the long term changes in higher education and their impact on traditional views of academia (see, for example, Adcroft & Willis, 2005). This paper aims to answer two broad questions.…”
Section: Introductionmentioning
confidence: 99%
“…They identify a number of studies carried out in the 1970s which suggested that the key motivations for students were based around issues such as "intellectual discovery", a "desire for knowledge" and "enthusiasm" (p.3) and argue that, for a number of reasons, this type of motivation is being eroded and replaced by more instrumental motivations whereby education has become "a means towards some end, rather than being valuable in its own right" (p.3). This is a reasonable reflection of a broad cross section of the literature which examines the long term changes in higher education and their impact on traditional views of academia (see, for example, Adcroft & Willis, 2005). This paper aims to answer two broad questions.…”
Section: Introductionmentioning
confidence: 99%
“…Neste ínterim, a ética na governação do princípio tradicional de bemestar público não se alinha com os negócios comerciais que visa ao bem-estar privado. Ao estabelecer uma lógica de mercado nas organizações públicas, a NAP contribui para a mercantilização dos serviços públicos (Adcroft & Willis, 2005); (b) orientação para o cliente ─ T. Diefenbach (2009) adverte que esta prática pode tornar o cidadão um coadjuvante nas decisões públicas, ou seja, um indivíduo que simplesmente exige pronta entrega de um serviço para suas próprias necessidades. Neste caso, observa-se uma inversão de importantes valores democráticos, pois o cidadão deve ser visto como um membro consciente e politicamente ativo do Estado, interessado nos assuntos públicos e no bem-estar de toda comunidade; (c) a NAP contribui para que o setor público perca sua neutralidade.…”
Section: Pressupostos Básicos E Elementos Essenciais Da Nova Administunclassified
“…Only a few of these journals actually concentrated on the unintended consequences as the main focus for research (Adcroft and Willis, 2005;Brigham and Fitzgerald, 2001;Humphreys and Francis, 2002;Shaffer, 1995;Tan and Rae, 2009). The remaining research mainly mentioned the presence of unintended consequences (Meyer, 2004;Powell et al, 2012;Unahabhokha et al, 2006).…”
Section: Unintended Consequences Of Regulation and Performance Measurmentioning
confidence: 99%